Pain between Psyche and Soma in Uro-Andrology - Pruneti Carlo; Guidotti Sara (International Journal of Pain Management, 2020)
How to define pain? One of the most accredited definition is certainly “An unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage
Keywords: pain